Possibilidades de diálogos sobre questões étnico-raciais em um grupo PIBID-Química - Pinheiro, Juliano Soares (2016)
This study aims to investigate and analyze the work done with a PIBID group - Chemistry / UFU, composed by the supervisory teacher and 7 undergraduate students in Chemistry who have developed 3 pedagogical actions: i) the use of the film "X-Men Origins: Wolverine" as a mediator between the chemical knowledge and the History of Africa; ii) the use of African mythology with the myth of Ogun for teaching about metals and chemical bounds; iii) the chemistry of hair interfaced with ethnic-racial theme. These actions aimed to establish connections between the teaching of chemical content and the ethnic-racial theme. Based on references by Multiculturalism Critic in Education and Education Studies of Ethnic-Racial Relations, this research falls under the prospect of a qualitative research, based on the proposition of the action-research methodology. Data were built through systematic monitoring of the constitution of actions involving participant observation, group interview, research journal and questionnaire. Data were analyzed according to content analysis proposed by Bardin (1977). Early in the preparation of the pedagogical actions, people in PIBID group - Chemistry had little knowledge of the Law 10.639 / 03, which created mistrust on how to establish links between chemical content and the ethnic-racial theme. Some challenges and difficulties were faced, concerning the school bureaucracy and the selection of chemical content that could make the connection with the ethnic-racial theme. The PIBID on this occasion has worked as a formative teaching element for the Education of Ethnic-Racial Relations. Working with the theme of Law 10.639 / 03 impacted the way people from PIBID group - Chemistry saw the African continent, its History and the African-Brazilian culture. The development of educational activities with the PIBID group - Chemistry held a training process that enabled the undergraduate students and the supervisor teacher glimpse ways to overcome simplistic views on History and African and African-Brazilian cultures.